KARAKTERISTIK KECEPATAN ALIRAN DI DEKAT DASAR PINTU PELUAPAN BAWAH (SLUICE GATE) - Laksitaningtyas, Agatha Padma; Legono, Djoko; Yulistiyanto, Bambang (Jurnal Teknik Pengairan, 2020)
Sluice Gates are the most important and often studied in hydraulic structures that are widely used and found, located in nature or artificial open channels. Sluice gates can be opened and closed at the bottom vertically. The sluice gate functions as a regulator of water flow which functions to control the discharge, control the water level and for monitoring the discharge. Water flowing through the sluice gate can be in a free flow condition or in a submerged flow condition that depends on depth of tailwater. The characteristics of the flow that flows through the sluice are based on the equation of energy and momentum conservation law, which depends on the pressure, velocity and depth of water that is upstream or downstream of the sluice. Hydraulics of sluice especially in free-flow conditions is very dynamic, including the profile of water level, the force that occurs on the sluice gate, or the velocity distribution of the bottom sluice gate, which is largely ignored. There are several basic development formulas of flows through the floodgates, especially in the development of vena contracta. Vena contracta will produce the values of the coefficient of discharge (Cd) and the coefficient of contraction (Cc) obtained from the calculation ratio of existing methods. Calculation of events theoretically and through experiments in the laboratory. However, the equation of discharge through the sluice gate is not very effective when used in a large opening condition and in a fully submerged condition.